Performance assessment of innovation infrastructure facilities in Russia - Vera Barinova; Alla Sorokina (European Regional Science Association (ERSA), 2014)
Performance assessment of innovation infrastructure facilities might be seen as one of the most topical issues of regional development in Russia. Due to the variety of infrastructure types, it's difficult to select the assessment indicators, for there are no generally accepted and integrated performance assessment measures, based on verifiable data according to the enquiries of the stakeholders. The article discusses ways to evaluate the efficiency of innovation infrastructure facilities in Russia. We assume, that innovation infrastructure can't be analyzed apart from the national innovation system it. It follows, that innovation infrastructure facilities performance is fully determined by the regional innovation system and its development. The aim was to find the optimum number of innovation infrastructure facilities, depending on the regions' level of innovative development. The research was based on the Miiris database (gathered by the National monitoring centre for innovation and scientific infrastructure and regional innovation systems), updated and enlarged. The total number of objects analyzed is 1158, situated in 75 regions of the Russian Federation, typically referred to technology&production (the most widespread group), consulting, financial and informational support, human capital (education), sales. To assess the sufficiency level authors use statistical methods for analyzing the relationship between the level of regional innovative development (defined according to the AIRR rating 2012) and the number of the innovation infrastructure facilities in Russian regions. The analysis has showed that the higher the level of regional innovative development is, the more innovation infrastructure facilities the region has. According to these results, the regions of Russia were divided into four groups: strong innovators (11), average+, average (28), average-, poor innovators (9). The analysis has also showed the possibility of determining the relevant number of innovative infrastructure facilities for each level of regional innovative development (defined by the regional innovative development index). This number demonstrates nonlinear growth from "poor" to "strong" innovators, that shows the synergy of the innovation potential accumulation in the regional economy. The important practical output is that building additional innovation infrastructure facilities in regions, described as "poor innovators", average- and in some cases average innovators - is ineffective, for there will be no demand for their services. In addition, authors propose a set of measures to improve the performance of the innovation infrastructure facilities, including the greater "soft infrastructure" involvement (ICT-facilities, social, professional and organizational networks) as the main way to enhance the private sector role in the regional innovative development.
Keywords: 330; Russian regions; innovation infrastructure; innovative development; ranking; performance indicators